Study on Halal Food Consumption, Integrity, Traceability, and Recommendations: Insights from Predominantly Islamized Groups in the Province of Cotabato, Philippines - Balah, Khadiguia Ontok; Makakena, Salik D. (Halal Center ITS, 2024)
The study focused on the perspectives on Halal food products of the three predominantly Islamized groups residing in the Cotabato Province, Philippines: Maguindanaon, Tausug, and Maranao. Three hundred heads of households served as the sample of the study. Data was gathered using a self-made survey questionnaire duly validated by Muslim scholars. The research revealed the participants’ strong preference for Halal-Certified products, ensuring adherence to Shari'ah Law. However, the participants’ concerns emerged regarding the lack of standardization and clear responsibility for Halal integrity. Transparency and traceability were identified as essential in the Halal food market, with the participants seeking accurate information and comprehensive traceability systems to prevent cross-contamination. Participants recommend strategic investments in Halal infrastructure, including storage and transportation processes that are crucial in Muslim-dominated regions like the Cotabato Province in the Philippines.